Effects of carbon amendment on in situ atrazine degradation and total microbial biomass - NGIGI, ANASTASIAH N.; GETENGA, ZACHARY M.; ULRIKE, D¨ORFLER; BOGA, HAMADI I.; KURIA, BENSON; NDALUT, PAUL (ARPN Journal of Agricultural and Biological Science, 2013)
This study elucidates the effects of carbon amendment on metabolic degradation of atrazine (6-chloro-N2-ethyl-N4-isopropyl-1,3,5triazine-2,4-diamine) and total microbial biomass in soil. Degradation of 14C-ring-labelled atrazine was monitored in laboratory incubations of soils supplemented with 0, 10, 100 and 1000 µgg −1 sucrose concentrations. An experiment to determine the effect of carbon amendment on total microbial biomass and soil respiration was carried out with different concentrations of sucrose and non-labelled atrazine. The soils were incubated at a constant temperature and constant soil moisture at water potential of−15 kPa and a soil density of 1.3 g cm−3. Mineralization of 14C-ring-labelled atrazine was monitored continuously over a period of 59 d in the ﬁrst experiment. The CO2 production was monitored for 62 d in the second experiment and microbial biomass determined at the end of the incubation period. The addition of 1000 µgg −1 sucrose reduced atrazine mineralization to 43.5% compared to 51.7% of the applied amount for the treatment without sucrose. The addition of 1000 µgg −1 sucrose modiﬁed the transformation products to 1.08 µgg−1 deisopropylatrazine (DIA), 0.32 µgg−1 desethylatrazine (DEA) and 0.18 µgg−1 deisopropyl-2-hydroxyatrazine (OHDIA). Treatment without sucrose resulted in formation of 0.64 µgg −1 hydroxyatrazine (HA), 0.28 µgg −1 DIA and 0.20 µgg −1 OH-DIA. Atrazine dealkylation was enhanced in treatments with 100 and 1000 µgg−1 of sucrose added. HA metabolite was formed inthecontrol(nosucrose)andinthepresenceof10 µgg−1 ofsucrose,whereasDEAwasonlydetectedintreatmentwith1000 µgg−1 sucrose. Results indicate that total microbial biomass increased signiﬁcantly (P < 0.001) with the addition of 1000 µgg−1 sucrose.
Keywords: Atrazine; carbon amendment; mineralization; metabolites; microbial biomass